A general and efficient approach for tuning the crystal morphology of classical MOFs. Issue 3 (7th December 2017) - Guo, Changyan; Zhang, Yonghong; Guo, Yuan; Zhang, Liugen; Zhang, Yi; Wang, Jide
Abstract : The size/morphology-controlled synthesis of classical MOFs with 2-methylimidazole (2-MI) as a coordination modulator. Abstract : This communication introduces a general approach toward the size/morphology-controlled synthesis of classical MOFs with 2-methylimidazole (2-MI) as a competitive ligand and a base to accelerate the nucleation of crystallization. A higher concentration of 2-MI and a suitable polarity and solubility of the solvent will accelerate the nucleation of the crystal, resulting in nanometer size particles. However, larger crystals can be obtained via the further growth of nanoparticles with prolonging the reaction time. Such a serendipitous discovery may inspire future researchers to design new MOF materials with desired structures.